GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Active phytoextraction of toluene shifts the microbiome and enhances degradation capacity in hybrid poplar - Michael BenIsrael; Dasiel Obregon; Philipp Wanner; Jeremy Fernandes; Joel G. Burken; Ramon Aravena; Beth L. Parker; Elizabeth A. Haack; David T. Tsao; Kari E. Dunfield (Journal of Environmental Management, 2025)

Impaired flexibility in decision making in rats after administration of the pharmacological stressor yohimbine - Andrea L. Schwager; Andrew K. Haack; Sharif A. Taha (Psychopharmacology, 2014)

TP53 gene polymorphism: Importance to cancer, ethnicity and birth weight in a Brazilian cohort - Helena S Thurow; Ricardo Haack; Fernando P Hartwig; Isabel O de Oliveira; Odir A Dellagostin; Denise P Gigante; Bernardo L Horta; Tiago Collares; Fabiana K Seixas (Journal of Biosciences, 2011)

Evidence for predominant clones in a cyclically parthenogenetic organism provided by combined demographic and genetic analyses - L. Haack; J.‐C. Simon; J.‐P. Gauthier; M. Plantegenest; C.‐A. Dedryver (Molecular Ecology, 2000)
Aphids are particularly interesting models in the study of genetic and demographic components of plant adaptation because of their breeding system which combines parthenogenesis and sexual reproduction (i.e. cyclical parthenogenesis), and the frequent emergence of host‐adapted races reported in this group. In this paper, patterns of host adaptation were assessed on local populations of the aphid Sitobion avenae by following their demographic and genetic structure in a maize field for two consecutive years. The existence of putative generalist (polyphagous) or specialized (host‐adapted) genotypes was also investigated by comparing the genotypic distribution of this aphid on maize and other cultivated host plants, using five microsatellite loci. Although population dynamics revealed strong variation in aphid abundance during the colonization period on maize, two genotypes identified at seven additional microsatellite loci were predominant and exhibited stable frequencies over cropping season and between years. Based on present and earlier studies, these two prevalent genotypes were shown to survive on different host plants other than maize, to colonize large geographical zones and to persist parthenogenetically for several years. All these data strongly suggest that these two genotypes are asexual generalist clones that could have been favoured by agricultural practices encountered in western Europe. Besides these two clones, a continual replacement of rare genotypes was observed on maize in both years. Hypotheses involving selection via aphid–plant interactions and natural enemies were proposed for explaining the disappearance of these genotypes on maize.